Socialization and Training on Organic Waste Shredding Machine for Waste Management in Schools - Dian Rahayu Jati; Jumiati Jumiati; Aini Sulastri; Herda Desmaiani; Ochih Saziati (International Journal of Public Devotion, 2026)
The issue of waste management remains a major challenge in Indonesia and has also extended to regional areas, including the City of Pontianak. The volume of waste in Pontianak City as of 2024 is recorded at 150,366 tons, this figure is the second largest in West Kalimantan Province. One of the waste-producing sectors is schools, with the composition of waste tending to vary according to the school's activities and geographical conditions. Generally, school organic waste consists of food scraps and leaves. This activity aims to increase the understanding of waste management and provide practical skills in the use of organic waste shredding machines. The implementation of this activity is carried out through several methods, namely (1) Socialization, (2) Demonstrati01101on of the Use of Machines, (3) Training and Composting, (4) Assistance and Maintenance. This activity was well organized, and evaluation results indicated that 80% of the participants were able to explain the functions and benefits of the shredding machine, and 70% were able to practice its use independently. The activity contributes to improving the skills of school residents in organic waste management. This activity is expected to be a reference for the application of environmental education with the implementation of simple technology in other target groups.Sosialisasi dan Pelatihan Mesin Pencacah Sampah Organik untuk Pengelolaan Sampah di Sekolah Kota PontianakABSTRAKPersoalan sampah selain masih menjadi tantangan di Indonesia, namun juga menyebar hingga ke daerah, termasuk Kota Pontianak. Volume sampah kota pontianak per tahun 2024 tercatat sebanyak 150,366 ton, angka ini kedua terbesar di Provinsi Kalimantan Barat. Salah satu sektor penghasil sampah adalah sekolah, dengan komposisi sampah cenderung beragam sesuai aktivitas dan kondisi geografis sekolah. Umumnya sampah organik sekolah terdiri dari sisa makanan dan daun-daun. Kegiatan ini bertujuan meningkatkan pemahaman pengelolaan sampah dan memberikan keterampilan praktis penggunaan mesin pencacah sampah organik. Pelaksanaan kegiatan ini dilakukan melalui beberapa metode, yaitu (1) Sosialisai, (2) Demonstrasi Penggunaan Mesin, (3) Pelatihan dan Pembuatan Kompos, (4) Pendampingan dan perawatan. Kegiatan ini terselenggara dengan baik, ditunjukkan hasil evaluasi bahwa 80% peserta mampu menjelaskan kembali fungsi dan manfaat mesin pencacah, serta 70% mampu mempraktikkan penggunaannya secara mandiri. Kegiatan berkontribusi pada peningkatan keterampilan warga sekolah dalam pengelolaan sampah organik. Kegiatan ini diharapkan dapat menjadi acuan untuk penerapan edukasi lingkungan dengan implementasi teknologi sederhana pada kelompok sasaran lainnya.Kata Kunci :edukasi lingkungan; kompos; mesin pencacah; sampah organik.